PERLINDUNGAN HUKUM KONSUMEN TENTANG ADANYA KLAUSULA BAKU DALAM KONTRAK ELEKTRONIK ANTARA KONSUMEN DAN PIHAK E-COMMERCE (STUDI KASUS PADA E-COMMERCE SHOPEE) - Prasetyo, Ade Jona; Saidin, Saidin; Kamello, Tan (Gorontalo Law Review, 2024)
E-commerce trade has become a reality in today's technology-driven society. This type of trade has undoubtedly brought changes to the system of buying and selling goods, especially in terms of contracts or agreements. E-commerce agreements tend to implement what is known as Standard Clauses. Standard Clauses in agreements are generally not allowed to include certain conditions that could harm the public, which is why they are regulated under Law Number 8 of 1999 concerning Consumer Protection as the legal basis for ensuring the rights and obligations of the parties involved. Therefore, it is necessary to investigate this issue. This thesis is titled â€œLegal Protection for Consumers Regarding Standard Clauses in Electronic Contracts Between Consumers and E-commerce Parties (Case Study on E-commerce Shopee)â€. The problem statements in this thesis are: 1) How is the implementation of Standard Clauses in electronic contracts in Indonesia? 2) How is the law applied in e-commerce transactions involving electronic contracts that include standard clauses and what are the legal consequences for consumers and business actors? 3) What are the responsibilities and dispute resolution mechanisms for business actors towards consumers if there is a discrepancy in the electronic contract in e-commerce transactions? The method used in writing this thesis is normative juridical research, which is legal research that examines library materials or secondary data as the basic material to be studied, while its nature is descriptive analytical. The research approach used is the statute approach. The data analysis method used is a qualitative method obtained from research on the study object, which is in the form of contracts or agreements linked to the prevailing laws and regulations. The research findings indicate that the application of Standard Clauses in contracts/agreements in e-commerce still has issues, particularly in cases of default. These issues occur in the form, timing, and quality of the goods being traded, causing consumers to sometimes be dissatisfied with the purchased goods. For these issues, there are mechanisms for business actors to be responsible for compensation as regulated in the Consumer Protection Act (UUPK), and there are three (3) consumer dispute resolution efforts, namely efforts outside the court such as mediation and negotiation, through BPSK, and efforts through the court such as filing lawsuits and others.